Enhanced Performance of Planar Perovskite Solar Cells Induced by Van Der Waals Epitaxial Growth of Mixed Perovskite Films on WS2 Flakes - Cao, Jiupeng; Tang, Guanqi; You, Peng; Wang, Tianyue; Zheng, Fangyuan; Zhao, Jiong; Yan, Feng (Advanced functional materials, 2020)
Organic–inorganic metal halide perovskite solar cells (PSCs) have attracted much research interest owing to their high power conversion efficiency (PCE), solution processability, and the great potential for commercialization. However, the device performance is closely related to the quality of the perovskite film and the interface properties, which cannot be easily controlled by solution processes. Here, 2D WS2 flakes with defect‐free surfaces are introduced as a template for van der Waals epitaxial growth of mixed perovskite films by solution process for the first time. The mixed perovskite films demonstrate a preferable growth along (001) direction on WS2 surfaces. In addition, the WS2/perovskite heterojunction forms a cascade energy alignment for efficient charge extraction and reduced interfacial recombination. The inverted PSCs with WS2 interlayers show high PCEs up to 21.1%, which is among the highest efficiency of inverted planar PSCs. This work demonstrates that high‐mobility 2D materials can find important applications in PSCs as well as other perovskite‐based optoelectronic devices. WS2 flakes are introduced as a template for van der Waals epitaxial growth of mixed perovskite films along (001) in perovskite solar cells with an inverted structure. Moreover, the WS2 interlayer forms a cascade energy alignment in the devices, which favors charge extraction and reduces interfacial recombination. The devices exhibit a power conversion efficiency up to 21.1% along with excellent stability.